Shocks and coping mechanisms in Climate-Smart Villages of the Nyando Basin, Kenya: Findings from a climate-smart agriculture (CSA) survey in Nyando Basin, Kenya - Rutto, Victor K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This Info Note summarizes the findings of a baseline survey of 122 smallholder farmers in the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) intervention areas of Nyando, Kenya. This is part of a bigger project entitled “Using Climate-Smart Financial Diaries for Scaling in Nyando,” led by the Amsterdam Center for World Food Studies (ACWFS) with the participation of CCAFS East Africa, University of Nairobi (School of Economics) and Wageningen Economic Research. The study analyzed the shocks that smallholder households experience, and their effect on household behavior. More specifically, we analyzed the effect of these shocks on diversification of CSA.